PERANAN PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DALAM MENINGKATKAN KEBERANIAN MENGEMUKAKAN PENDAPAT SISWA - Marlina, Lina (Universitas Negeri Manado, 2019)
This research starts from the problems that appeared in Citizenship Education learning process which is recognized by lack of students’ activeness and low of courage level in expressing students’ opinions. The indication of lack the courage in expressing students’ opinions can be seen from the low of students’ activeness in learning process. Teachers have the most strategic role in learning process. The teachers Strategic role in learning process have the impact on students' competencies (knowledge, attitudes, skills). The competence of students’ will develop optimally depending on how teachers place them selves and students’ in teaching learning process. Based on the background above, the identification of this research formulation is how the teaching and learning of Citizenship Education can play an important role in improving the courage for the students’ to be able express opinions during the teaching-learning process easily. This research was conducted by the purpose to know how the Citizenship Education can play an important role in improving the courage to express students opinions in teaching-learning process. To achieve the objectives conducted qualitative research on the case study method of learning Citizenship Educationin at Vocational High School Pasundan I Serang City. Data collecting technique that used were observation, interview and documentation. From the result of analysis, it can be concluded that Citizenship Education in improving the courage express students opinions is able to change the situations of learning centere on teachers become students active role in achieving the learning objectives. Based on the findings of this research, it can be argued that the Citizenship Education in improving the courage to express students opinion have the potential to participate actively in the learning process and collaboration in a heterogeneous group.Keywords: learning, Citizenships Education, Courage, Expressing Opinions